แนวทางการป้องกันอุทกภัยสำหรับโครงการอสังหาริมทรัพย์ในแนวราบ กรณีศึกษา : โครงการพฤกษ์ลดา วงแหวน-รัตนาธิเบศร์ และโครงการพฤกษ์ลดา 2 บางใหญ่ - ชัยยงค์ ภูษณพิทักษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The flood in 2011 caused massive damage to both the Thai economy and society. The damage cost many hundred thousand baht as well as hundreds of lives. People living in the flooded areas suffered considerable property damage. This caused up to 1 trillion baht in damage to the allocated houses . More than 5.4 hundred thousand allocated housing units were flooded affecting residents of Bangkok and vicinity. The objectives of this study were to study flood protection methods for the rise real estate. The study focused on flood conditions in allocated housing project areas, approaches for protecting the projects from flooding, and the impact on the residents of the projects. The methodology included interviews with project engineers and residents, observations, recordings, and photographing. The data obtained were analyzed together with relevant theories and studies in order to find out the best approaches for preventing flooding of rise real estate. A study of flood conditions in the area of the allocated project, Pruklada Wongwaen -Rattanathibet, show that the area is a basin with 3 canals surround. During the flooding period, these canals overflowed with the level of floodwater surrounding the project being 1.00 meter in depth. The soil fill was 0.50 meter higher than the level of the road in front of the project. As for the Pruklada 2 Bangyai Project, its location was higher than the Pruklada Wongwaen -Rattanathibet Project with Bangrak Yai – Banmai Road serving as a natural barrier. The level of floodwater was 0.55 meters from the front of the project. Regarding approaches in place to protect against the flood, the Pruklada Wongwaen -Rattanathibet Project was in the process of establishing a project committee when the flood occurred. The fence around the project was a post and beam system which was molded in-house with a laterite wall. During the flooding, water had streamed through the laterite wall and beams of the project. In addition, the soil fill had collapsed in some parts where the stagnant water was high and the utility system had been soaked. There was a misunderstanding regarding flood management information when the residents in the project had renovated their building. As a result, the project was more vulnerable to the flood As the Pruklada Wongwaen -Rattanathibet Project was completely flooded, it affected the residents socially and economically, before, during, and after the flooding. This impact was more severe than that of the Pruklada 2 Bangyai Project. Although there was no stagnant water in the project, it still affected the residents because the surrounding areas retained a high level of stagnant water. The transportation was inaccessible, and the electricity from the Provincial Electricity Authority was shut down. Recommendations for approaches to protect against flooding in these projects focus on 2 areas, which are measures for buildings and non-building measures. Both types of measures play a major role in protection in the area of construction, fences of the project, and utility systems which must be a closed system. As for management, information provided should be straightforward and housing units must be insured. An interesting point for further research would be to study the structural design of the projects in order to have long-term protection.